Religious research in the first years of independence - Ф.Т., Жумажанова (Journal of Oriental Studies, 2020)
The culture and literature of each nation are characterized by its own “path” of growth, the method of formation and characteristics of development. The Kazakh literature was no exception, accordingly, it was closely developed with the traditional religious beliefs of the Kazakh society. The close connection of our national literature with religion almost began from the moment of the formation of the Kazakh people and included the period of Soviet power. After gaining independence, Kazakhstan faced the task of reviving the rich spiritual heritage of the Kazakh people. The article discusses materials that have become available to the public only after independence. With the independence of the state, the Kazakh people began to gradually revive the religion that was banned during the years of Soviet power and thus gradually returned to Islam. In addition, the author included in this study several religious works prepared in the early years of independence. Key words: beliefs, customs, Islam, religious studies, literary heritage, religious values.